Analisis Prediksi Kebangkrutan Dengan Menggunakan Metode Springate Pada PT Saranacentral Bajatama Tbk Periode Tahun 2016-2021 - Thoharoh, Muchibatut; Haeruddin, Muh. Ikhwan Maulana; Nurman; Ramli, Anwar; Anwar (CV. Lafadz Jaya, 2023)
Bankruptcy prediction using the springate method is one way that companies can do to determine company bankruptcy. The goal is that the company can find out the potential for bankruptcy of the company in a certain year or period and also the company can find out what things can put the company in the danger zone or have the potential to go bankrupt. In this study, the type of research used is descriptive quantitative and the research method used is the springate method with the variables consisting of 4 ratios, namely the ratio of working capital to assets (X1), the ratio of earnings before interest and taxes to total assets (X2), the ratio profit before tax to total current liabilities (X3) and ratio of sales to total assets (x4). The results of the calculations from this study are that from 2016 to 2019 the company is in the danger zone or has the potential to go bankrupt but in the last 2 years, namely in 2020 and 2021 the company started in fairly good condition or there is no potential for bankruptcy at the company.